Optical measurement of characteristics of thin films using a spiral zone plate - Nalimov, A.G.; Kozlova, E.S.; Stafeev, S.S.; Kotlyar, V.V.; Podlipnov, V.V. (Kompʹûternaâ optika, 2025)
In this work we propose a method for measuring physical characteristics of thin samples (thin films), including thickness, refractive index and tilt by moving the observation plane. The measurements are made utilizing a vortex spiral zone plate, which forms three intensity maxima that rotate when moving along optical axis. The error in measuring the tilt of a sample is a fraction of a degree, and the error in measuring its thickness is less than 5 nm. By the numerical simulation, three intensity maxima are shown to be formed after a metalens, rotating in space with an angular velocity of 136°/μm, which is almost twice as high as was reported in similar works.